Effect of fish protein, salt, sugar, and monosodium glutamate on the gelatinization of starch in fish-starch mixtures - Chong, Seng Cheow; Swee, Yean Yu (Food and Nutrition Press Inc., 1997)
Differential Scanning calorimetry (DSC) was used to study the effect of fish protein, salt, sugar, and monosodium glutamate (MSG) on gelatinization of tapioca and sago starches in fish cracker mixtures. One endothermic transition was observed for fish-starch mixtures (10-90% wet fish) if the moisture content was more than 61%. The effect of the salt on the starch gelatinization is greater than sugar and MSG. Sugar and MSG addition to the mixture had little effect on gelatinization of starch in the system. Two percent salt increased the gelatinization temperature by 4-5 C. The onset (T0) and peak (Tp) temperatures increased with increases in fish content in fish-starch mixtures but the conclusion temperatures (Tc) remained relatively constant. Increases in fish content also narrowed the gelatinization temperature ranges.